Disruptive technologies: Integration in existing supply chain processes - Stephanie Niehues; Tan Gürpinar (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: Based on technological progress, companies innovate and design a variety of new processes to be implemented in order to gain a competitive advantage. Nevertheless, many companies face issues during the initial integration of these emerging technologies with their existing business processes. This paper will collect and analyze existing procedures to leverage process innovations by means of emerging information- and production technologies with disruptive potential. Methodology: An exploratory research of relevant procedures for the implementation of new processes is chosen to give a systematic overview of existing models. Furthermore, requirements for the technology integration of emerging information technologies and production technologies are collected within a systematic content analysis and based on these requirements, the existing models are compared and evaluated. Findings: None of the existing models meet the requirements of a technology-based integration of process innovations. In order to integrate particularly emerging technology based innovations into business processes, existing models must be further developed, particularly with regard to the flexibility requirements of industry 4.0 process changes. Originality: This paper collects and compares all important models for the implementation of process innovations, based on requirements specific to the integration of emerging information- and production technologies. Blockchain technology and additive manufacturing are used as exemplary current technologies with disruptive potential.
urn:nbn:de:gbv:830-882.054275; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Process innovations; Blockchain; Additive manufacturing; Supply chain